Nilai dalam Ritual Adat Kayori Pompaura Sindue (Pembelajaran Nilai Sosial) - Nirmayanti; Efendi; Nur Halifah (Jurnal Kreatif Online, 2022)
The traditional ritual of Kayori Pompaura in Marana village, Sindue district, Donggala regency, Central Sulawesi Province is one of the traditional rituals of the Kaili Rai tribe in Sindue. This Kayori Pompaura traditional ritual has different characteristics from other traditional rituals. Kayori Pompaura's traditional ritual is carried out by humming. Kayori is an anonymous type of traditional song. The hallmark of Kayori is that it is always hummed by involving many people. Therefore, Kayori requires good cooperation in every implementation. The purpose of this study is to describe the social values contained in the traditional ritual of Kayori Pompaura Sindue (Social Values Learning). The results of the study can be used as learning material for social values in schools by looking at the aspects of social values contained in the implementation of the Kayori Pompaura Sindue traditional ritual. This research is a type of qualitative descriptive research because the Kayori Pompaura traditional ritual has a natural background and the data is in the form of words (oral and written). The social values contained in Kayori Pompaura's oral literature are material values, vital values, and spiritual values. In the aspect of spiritual values, it is divided into four parts, namely the value of goodness, religious value, value of truth and value of beauty.